Sustainable Agriculture 2009
DOI: 10.1007/978-90-481-2666-8_12
|View full text |Cite
|
Sign up to set email alerts
|

Plant Drought Stress: Effects, Mechanisms and Management

Abstract: -Scarcity of water is a severe environmental constraint to plant productivity. Drought-induced loss in crop yield probably exceeds losses from all other causes, since both the severity and duration of the stress are critical. Here, we have reviewed the effects of drought stress on the growth, phenology, water and nutrient relations, photosynthesis, assimilate partitioning, and respiration in plants. This article also describes the mechanism of drought resistance in plants on a morphological, physiological and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
1,245
4
40

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,336 publications
(1,331 citation statements)
references
References 226 publications
42
1,245
4
40
Order By: Relevance
“…Among the abiotic stresses, drought has a crucial devastating impact on agricultural production (Farooq et al 2009;Farooq et al 2012). Plants recruit complex overlapping mechanisms to reprogram their gene expression to cope with drought stress (Ahuja et al 2010;Golldack et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Among the abiotic stresses, drought has a crucial devastating impact on agricultural production (Farooq et al 2009;Farooq et al 2012). Plants recruit complex overlapping mechanisms to reprogram their gene expression to cope with drought stress (Ahuja et al 2010;Golldack et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These increments would be attributed to the major role of the applied microelements in photosynthesis activation, pigments formation and carbohydrates assimilation converted to the grains which optimize the economic part of the plant (Hilman & Asandhi, 1987). Farooq et al (2009) reported that water stress leads to severe decrease in yield components of crop plants probably by disrupting leaf gas interchange properties which not only restricted the size of the source and sink tissue show ever the phloem loading, assimilate translocation and dry matter distribution are also impaired. Thalooth et al (2006) illustrated that the foliar spray with zinc sulfate under drought condition have the positive effect on yield and its components of mungbean plant.…”
Section: Yield and Its Componentsmentioning
confidence: 99%
“…When plant expose to adverse environment (drought) reactive oxygen species (ROS) such as superoxide (O 2 • ), hydrogen peroxide (H 2 O 2 ), hydroxyl radicals (OH • ) and singlet oxygen ( 1 O 2 ) are produced (Faize et al 2011). Multiple antioxidant enzymes like superoxide dismutases (SOD), catalases (CAT) and peroxidases (POX) are involved in the enzymatic scavenging of ROS (Apel and Hirt, 2004;de Carvalho, 2008;Farooq et al 2009). (Jiang and Jhang, 2004).…”
Section: Issn: 2319-7706 Volume 7 Number 04 (2018)mentioning
confidence: 99%